Triple threat [videorecording (DVD)] - Johnson, Jesse V., 1971-; Jaa, Tony, 1976-; Jade, Celina, 1985-; White, Michael Jai (Well Go USA Entertainment, 2019)
When a hit contract is taken out on a wealthy woman trying to bring down a crime syndicate, a team of wanted mercenaries fights a group of professional assassins over their target.